A possible Fourier transform infrared‐based plasma fingerprint of angiotensin‐converting enzyme inhibitor‐induced reversal of endothelial dysfunction in diabetic mice. Issue 2 (31st July 2017) - Staniszewska‐Slezak, Emilia; Wiercigroch, Ewelina; Fedorowicz, Andrzej; Buczek, Elżbieta; Mateuszuk, Lukasz; Baranska, Malgorzata; Chlopicki, Stefan; Malek, Kamilla
Abstract : Angiotensin‐converting enzyme inhibitors (ACE‐I) display vasoprotective activity and represent the cornerstone in the treatment of cardiovascular diseases. In this study, we tested whether Fourier transform infrared (FTIR)‐based analysis of blood plasma is sensitive to detect vasoprotective effects of treatment with perindopril including reversal of endothelial dysfunction in diabetes. For this purpose, plasma samples were collected from untreated db/db mice, db/db mice treated with 2 or 10 mg/kg perindopril and db+ mice. The effect of perindopril on endothelial function was examined in ex vivo aortic rings; 10 mg/kg but not 2 mg/kg of perindopril reversed endothelial dysfunction. In plasma of db/db mice, the balance between conformations of plasma proteins was noted, and treatment with perindopril at a high dose but not at a low dose reversed this effect. This was revealed by amide II/amide I ratio attributed to increased β‐sheet formation. Spectral markers at 3010, 1520/1238 cm −1, representative for unsaturation degree of lipids and phosphorylation of tyrosine, respectively, were also affected by perindopril treatment. In conclusion, although metabolic abnormalities associated with type 2 diabetes mellitus such as hypertriglyceridemia and hyperglycemia strongly affected spectral FTIR profile of diabetic plasma, we identified FTIR features that seem to be associated with the vasoprotective activity of ACE‐I. Abstract : This work describes an attempt to assess the changes in the FTIR spectra of plasma of diabetic mice (db/db) treated with ACE‐I (perindopril) given at 2 and 10 mg/kg daily dose for 4 weeks. In particular our aim was to differentiate FTIR‐based profile of plasma samples between the diabetic and control group, and to analyse the FTIR‐based spectra of plasma that could reflect vasoprotective effects of perindopril treatment, evidenced by the reversal of endothelial dysfunction.